(untitled) (Scientific journal of the Fergana State University, 2026)
This article contains information about the adoption of the “Madrasa Program” in the Turkestan region, the tasks of determining the qualifications of teachers, the age of students, and their attitude to learning, adapting buildings to modern school buildings, as well as the fact that, under pressure from the Communists, the People’s Ministry of Education of the USSR, in agreement with the government, issued a regulation on the “Madrasa Reform” in May 1920, using endowment income mainly for the social needs of madrasas, and establishing the teaching of secular sciences in madrasas along with religious sciences.